An adhesive containing an epoxy-terminated polyurethane epoxy resin and a preparation method and application thereof
Patent Information
- Application Number
- CN202511110588.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-08
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-08-08
AI Technical Summary
然而,传统环氧树脂胶粘剂存在两个显著缺陷:其一,固化过程中会产生较高的放热峰值
[0033](1)本发明的环氧封端聚氨酯环氧树脂打破了原环氧树脂刚性交联结构的束缚,延缓了和胺固化剂交联反应的速度,彻底消除了体系中的残留的-NCO基团;
Smart Images

Figure BDA0005539752730000031 
Figure BDA0005539752730000051 
Figure BDA0005539752730000071
Abstract
Description
Technical Field
[0001] This invention relates to the field of adhesive technology, and in particular to an adhesive containing epoxy-terminated polyurethane epoxy resin, its preparation method, and its application. Background Technology
[0002] Epoxy resin adhesives are widely used in aerospace, electronics, and machinery manufacturing due to their high strength, good chemical stability, and excellent bonding performance. However, traditional epoxy resin adhesives have two significant drawbacks: First, they generate high exothermic peaks during curing. As the crosslinking density increases rapidly when epoxy resin reacts with the amine curing agent, a large amount of reaction heat accumulates in a short time, leading to a sharp increase in local temperature (typically reaching 120-150℃). The thermal stress generated during curing can cause defects such as cracks and pores within the material, and may also cause thermal damage to the bonded heat-sensitive materials (such as electronic components and polymer composites), affecting their performance and service life, thereby reducing the material's mechanical properties and durability. Furthermore, for large-sized products, excessively rapid exothermic reactions can easily lead to excessively high local temperatures and uneven curing, thus affecting product quality consistency. Second, epoxy resin itself has high molecular chain rigidity and high crosslinking density, resulting in poor toughness of the cured material, with an elongation at break typically below 5%. When subjected to stress caused by impact, vibration, or temperature changes, adhesives are prone to brittle fracture, leading to bonding failure.
[0003] To address these issues, existing technologies primarily employ methods such as adding toughening agents or altering the curing system. For instance, while adding toughening agents like rubber elastomers or thermoplastic resins can improve toughness to some extent, it often leads to a decrease in strength and is prone to phase separation, affecting the overall performance of the adhesive. Adjusting the type or ratio of curing agents to reduce exothermic peaks has limited effectiveness and may prolong curing time, reducing production efficiency.
[0004] Furthermore, patent CN 116285831 A (application number: 202211513435.7) discloses a polyurethane-modified epoxy resin adhesive and its preparation method. By reacting epoxy resin with a polyurethane prepolymer to generate an EP-PU grafted IPNs structure, the toughness and fatigue resistance of the adhesive are improved, while also improving storage capacity and addressing foaming issues during construction. However, this technology still has the following shortcomings: First, when the polyurethane prepolymer reacts with the epoxy resin, the NCO groups may not be completely consumed, thus forming potential reactive sites in the system and failing to fundamentally solve the foaming problem. Second, although this technology optimizes energy consumption by lowering the reaction temperature and shortening the reaction time, its control over the exothermic peak is limited, and it still cannot completely avoid the problem of localized heat accumulation. Third, although its elongation at break is improved (greater than 6.55%), further improvements are still needed for certain applications requiring high toughness.
[0005] Therefore, the exothermic peak of epoxy resin adhesives needs to be reduced, the toughness needs to be improved, and the foaming problem caused by NCO residue still needs to be solved. Summary of the Invention
[0006] Objectives of the Invention: The first objective of this invention is to provide an epoxy-terminated polyurethane epoxy resin that eliminates NCO residue and exhibits a slow crosslinking rate during reaction with an amine curing agent; the second objective is to provide a method for preparing the epoxy-terminated polyurethane epoxy resin; the third objective is to provide an adhesive containing epoxy-terminated polyurethane epoxy resin that reduces exothermic peak values, improves toughness, and avoids foaming problems caused by NCO residue; the fourth objective is to provide a method for preparing the adhesive; and the fifth objective is to provide applications of the adhesive.
[0007] The epoxy-terminated polyurethane epoxy resin of the present invention is obtained by reacting a polyurethane prepolymer and an epoxy resin, wherein the NCO of the polyurethane prepolymer and the hydroxyl groups of the epoxy resin undergo an addition reaction, and after the reaction, a small molecule epoxy compound is used to eliminate the NCO in the system; the polyurethane prepolymer is obtained by reacting an isocyanate and a segmentally flexible polyether polyol.
[0008] The NCO content in the polyurethane prepolymer is 5-6%; in the reaction between the polyurethane prepolymer and the epoxy resin, the amount of NCO added to the system by the epoxy resin is 2-3%.
[0009] In the epoxy-terminated polyurethane epoxy resin of the present invention, the NCO of the polyurethane prepolymer reacts only with the hydroxyl groups in the epoxy resin and not with the epoxy groups, thus preserving the integrity of all epoxy groups in the epoxy resin. This provides a pure epoxy reserve for the subsequent epoxy-terminated reaction of glycidyl ether, avoiding ring-opening side reactions of the epoxy groups (such as the formation of ether bonds or tertiary bonds). Ultimately, this ensures that the resin structure is well-defined and controllable, achieving a well-defined block structure of "polyurethane flexible chain" and "epoxy rigid end group", which, after curing with the curing agent, forms an ideal topology of "flexible bridged rigid network".
[0010] Preferably, the segmentally flexible polyether polyol is at least one of polypropylene oxide polyol (PPG), polytetrahydrofuran polyol (PTMEG), or polyethylene oxide-propylene oxide copolyol.
[0011] The epoxy resin is at least one of bisphenol A type epoxy resin and bisphenol F type epoxy resin.
[0012] Preferably, the small molecule epoxy compound is glycidol.
[0013] Preferably, the isocyanate is toluene diisocyanate (TDI-80) or isophorone diisocyanate (IPDI).
[0014] The preparation method of the epoxy-terminated polyurethane epoxy resin of the present invention includes the following steps:
[0015] (1) Dehydrate the segmentally flexible polyether polyol and then react it with isocyanate at 70-80°C under inert gas protection for 2-3 hours to obtain polyurethane prepolymer.
[0016] (2) Add epoxy resin to the polyurethane prepolymer and react at 60–70°C for 2–3 hours; add small molecule epoxy compound dropwise, add organotin catalyst, and react at 50–55°C until the NCO groups completely disappear to obtain epoxy-terminated polyurethane epoxy resin. The synthesis route is as follows:
[0017]
[0018] Preferably, in step (1), the dehydration conditions of the polyether polyol are: dehydration at 110-120°C and vacuum degree -0.095MPa for 2-3 hours.
[0019] In step (2), the reaction of bisphenol A epoxy resin with polyurethane prepolymer at 60-70°C for 2-3 hours is to prevent epoxy ring opening and to consume some of the -NCO groups of polyurethane prepolymer to complete molecular chain extension; the slow addition of small molecule epoxy compound is to completely consume the -NCO groups of polyurethane prepolymer to complete epoxy end capping; the addition of organotin catalyst is to promote the reaction of small molecule compound with -NCO groups, and the reaction at 50-55°C is to control selectivity at low temperature.
[0020] Preferably, in step (2), the organotin catalyst is at least one of dibutyltin dilaurate (DBTDL) or stannous octoate.
[0021] The adhesive of the present invention containing the epoxy-terminated polyurethane epoxy resin comprises the following components by weight: 10-15 parts epoxy resin, 70-75 parts epoxy-terminated polyurethane epoxy resin, 19-21 parts amine curing agent, and 8-15 parts thermally conductive filler.
[0022] The epoxy resin is at least one of bisphenol A type epoxy resin and bisphenol F type epoxy resin.
[0023] Preferably, the thermally conductive filler is at least one of alumina, aluminum hydroxide, or aluminum nitride.
[0024] Preferably, the amine curing agent is at least one of isophorone diamine (IPDA), cycloethylenediamine (CHDA), m-phenylenediamine (MPDA), or p-phenylenediamine (PPDA).
[0025] The method for preparing the adhesive of the present invention includes the following steps:
[0026] (1) Mix the epoxy resin, epoxy-terminated polyurethane epoxy resin and thermally conductive filler evenly;
[0027] (2) Add an amine curing agent and mix for 30 seconds at a vacuum of ≤-100kPa and a rotation speed of 1200RPM to obtain an adhesive.
[0028] The adhesive described in this invention has applications in the fields of aerospace, electronics, electrical appliances, or machinery manufacturing.
[0029] Invention Mechanism:
[0030] The epoxy-terminated polyurethane epoxy resin of this invention introduces flexible segments. On the one hand, these flexible segments can delay the crosslinking reaction during the reaction between the epoxy-terminated polyurethane epoxy resin and the amine curing agent. On the other hand, the flexible polyether polyols possess excellent flexibility and adaptability. After these segments are incorporated into the epoxy resin network, they can break the constraints of the original rigid crosslinking structure of the epoxy resin. Furthermore, the epoxy-terminated polyurethane epoxy resin of this invention completely eliminates residual -NCO groups in the system.
[0031] The adhesive of this invention incorporates the epoxy-terminated polyurethane epoxy resin. The flexible polyether segments in the epoxy-terminated polyurethane epoxy resin hinder the rapid crosslinking of the epoxy resin during curing, reducing the crosslinking reaction rate, delaying heat release, and thus lowering the exothermic peak. Adding thermally conductive fillers to the adhesive, with their high thermal conductivity, effectively conducts the heat generated by the curing reaction, preventing localized heat accumulation and further reducing the system's exothermic peak. The introduction of flexible segments into the epoxy-terminated polyurethane epoxy resin breaks the constraints of the original rigid crosslinking structure of the epoxy resin. When the adhesive is stretched by external force, the flexible segments can absorb energy through the extension and slippage of the molecular chains, thereby significantly improving the material's elongation capacity. The epoxy-terminated polyurethane epoxy resin of this invention, through a chemical end-capping process, completely eliminates residual -NCO groups in the system, fundamentally solving the material foaming problem. Furthermore, the adhesive incorporates both epoxy-terminated polyurethane epoxy resin and epoxy resin. Through the reaction of epoxy groups with the curing agent, the polyurethane segments are firmly linked to the epoxy resin network via chemical bonds, avoiding the phase separation problems caused by simple physical blending. The flexible segments in the epoxy-terminated polyurethane resin can improve the brittleness of the epoxy resin, enhancing the material's impact resistance and flexibility. The rigid structure of the epoxy resin maintains the tensile strength and hardness of the material, preventing excessive softening. This ensures that the adhesive maintains high bonding strength and stability while improving toughness.
[0032] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0033] (1) The epoxy-terminated polyurethane epoxy resin of the present invention breaks the constraint of the rigid cross-linking structure of the original epoxy resin, slows down the cross-linking reaction with the amine curing agent, and completely eliminates the residual -NCO groups in the system.
[0034] (2) The preparation method of the epoxy-terminated polyurethane epoxy resin of the present invention is simple and easy to industrialize;
[0035] (3) The adhesive containing epoxy-terminated polyurethane epoxy resin of the present invention reduces the exothermic peak value by 25-50°C, avoids heat damage and uneven curing of heat-sensitive materials, and improves the quality consistency of large-size products; significantly improves toughness: the elongation at break is greater than 7%, solving the problem of brittle fracture of traditional epoxy resin, enhancing the adhesive's resistance to impact and vibration, and adapting to dynamic stress scenarios; maintains high strength: the tensile strength is maintained above 66.9 MPa, achieving a balance of "high toughness-high strength", overcoming the drawback of strength reduction caused by toughening agents; eliminates foaming risks: the chemical end-capping process completely consumes NCO groups, avoiding foaming from the source, and at the same time, integrates polyurethane and epoxy resin through chemical bonds to prevent phase separation and improve stability;
[0036] (4) The adhesive containing epoxy-terminated polyurethane epoxy resin of the present invention has the following process adaptability: the raw material selection is flexible (polyether, thermally conductive filler, etc. can be adjusted), the process is simple, it is suitable for large-scale production, and meets the demanding performance requirements of aerospace, electronics and electrical appliances and other scenarios. Detailed Implementation
[0037] The present invention will be further described below with reference to specific embodiments.
[0038] Information on the raw materials used in this invention is shown in Table 1.
[0039]
[0040] Example 1
[0041] The adhesive containing epoxy-terminated polyurethane epoxy resin of the present invention is prepared by the following steps:
[0042] (1) PTMEG-2000 was placed in a reactor and dehydrated for 3 hours at 110°C and a vacuum of -0.095 MPa to remove moisture from the raw material and prevent side reactions between moisture and isocyanate. 100 parts by weight of the dehydrated PTMEG-2000 were taken, and then 24 parts by weight of TDI-80 were added. Nitrogen gas was introduced for protection, and the mixture was stirred and reacted at 80°C for 2 hours to obtain a polyurethane prepolymer with an NCO content of 6%.
[0043] (2) According to the weight percentage, add 70 parts of E-44 (the NCO content of the system is 3% after the addition) to the above 20 parts of polyurethane prepolymer, and react at 60°C for 3 hours; slowly add 10 parts of glycidyl ether at a rate of 50 mg / min, and at the same time add 0.05 parts of DBTDL, and react at 50°C until the NCO in the system disappears, to obtain epoxy-terminated polyurethane epoxy resin.
[0044] (3) Weigh 75 parts of the synthesized epoxy-terminated polyurethane epoxy resin, 10 parts of bisphenol A epoxy resin E-44 and 15 parts of filler alumina according to the weight ratio. Mix them at high speed at 700 RPM for 10s to form component A. Add 19 parts of isophorone diamine to component A and evacuate to a pressure below -100 kPa. Mix them at high speed at 1200 RPM for 30s to prepare epoxy-terminated polyurethane epoxy adhesive.
[0045] Example 2
[0046] The similarities between this embodiment and Embodiment 1 will not be repeated here. The difference is that PPG-2000 is used instead of PTMEG-2000 (the NCO content of the system is 6% after its addition).
[0047] Example 3
[0048] The similarities between this embodiment and Embodiment 1 will not be repeated here. The difference is that the amounts of epoxy-terminated polyurethane epoxy resin, epoxy resin E-44, alumina, and isophorone diamine are 70 parts, 15 parts, 15 parts, and 19 parts, respectively.
[0049] Example 4
[0050] The similarities between this embodiment and Embodiment 1 will not be repeated here. The difference is that the amounts of epoxy-terminated polyurethane epoxy resin, epoxy resin E-44, alumina, and isophorone diamine are 75 parts, 10 parts, 8 parts, and 19 parts, respectively.
[0051] Example 5
[0052] The similarities between this embodiment and Embodiment 1 will not be repeated here. The difference is that aluminum hydroxide is used instead of aluminum oxide.
[0053] Example 6
[0054] The similarities between this embodiment and Embodiment 1 will not be repeated here. The difference is that aluminum nitride is used instead of aluminum oxide.
[0055] Example 7
[0056] The similarities between this embodiment and Embodiment 1 will not be repeated here. The difference is that the amounts of epoxy-terminated polyurethane epoxy resin, epoxy resin CYDF-170, isophorone diamine, and alumina are 75 parts, 10 parts, 21 parts, and 8 parts, respectively.
[0057] Comparative Example 1
[0058] According to the weight parts, 85 parts of bisphenol A epoxy resin E-44 and 19 parts of isophorone diamine were weighed and mixed at high speed for 30 seconds at 1200 RPM under vacuum to a pressure below -100 kPa to prepare epoxy resin adhesive.
[0059] Comparative Example 2
[0060] According to the weight parts, 85 parts of epoxy resin CYDF-170 and 21 parts of isophorone diamine were weighed and mixed at high speed for 30 seconds at 1200 RPM under vacuum to a pressure below -100 kPa to prepare epoxy resin adhesive.
[0061] Comparative Example 3
[0062] Based on Example 1, in step (2), glycidyl ether was not used for end-capping, some NCO groups were retained, and the other conditions remained unchanged to prepare an epoxy resin adhesive.
[0063] Comparative Example 4
[0064] Based on Example 1, in step (2), 70 parts of E-44 were added to the above 20 parts of polyurethane prepolymer, and the reaction was carried out at 90°C until the NCO in the system disappeared.
[0065] Comparative Example 5
[0066] Based on Example 1, in step (1), non-flexible polyether 670BA is used instead of flexible polyether PTMEG-2000.
[0067] Comparative Example 6
[0068] Based on Example 1, in step (3), the amounts of epoxy-terminated polyurethane epoxy resin, epoxy resin E-44, alumina, and isophorone diamine added are 85 parts, 0 parts, 15 parts, and 19 parts, respectively.
[0069] Performance testing
[0070] The samples obtained in Examples 1-7 and Comparative Examples 1-6 were subjected to performance tests, including tensile strength, elongation at break, viscosity, and exothermic peak. The test methods are as follows.
[0071] Tensile strength: Cured at 25℃ for 7 days, tested according to GB / T 528-2009.
[0072] Elongation at break: Cured at 25℃ for 7 days, tested according to GB / T 528-2009.
[0073] Exothermic peak: The precise exothermic peak was obtained by DSC testing (heating rate 10℃ / min).
[0074] Foaming phenomenon: After component A is exposed to air for 48 hours, visually inspect for the formation of bubbles.
[0075] The test results for each sample are shown in Table 1.
[0076] Table 1 Test results for each sample
[0077]
[0078] The adhesives in Examples 1-7 all exhibited strengths ≥66.9 MPa, toughness ≥7%, and exothermic temperatures ≤115°C, with no foaming observed. This is because the epoxy adhesive performance was comprehensively optimized through epoxy-terminated polyurethane modification and the introduction of thermally conductive fillers, achieving a synergistic optimization of high strength, high toughness, and low exothermic temperature. This overcomes the contradiction of decreased strength or excessive exothermic temperature in traditional toughening technologies. Furthermore, the chemical end-capping process ensures complete consumption of NCO groups, thus avoiding foaming issues.
[0079] Compared to Examples 1-7, Comparative Examples 1-2 did not use modified epoxy resin and thermally conductive fillers. The epoxy resin crosslinking reaction was intense, resulting in concentrated exothermic reactions and high peak values. The exothermic peak values of Examples 1-7 were 80-115℃, significantly lower than Comparative Example 1 (130℃) and Comparative Example 2 (140℃). Higher thermal conductivity of the thermally conductive filler resulted in better exothermic control (aluminum nitride > aluminum oxide > aluminum hydroxide). Among these, Example 6, using aluminum nitride (high thermal conductivity 150-220 W / (m·K)), had the lowest exothermic peak value (80℃), indicating that the thermally conductive filler effectively conducts heat. Combined with the flexible segments of the epoxy-terminated polyurethane, which hinder rapid crosslinking, this synergistically reduces the exothermic peak value.
[0080] The elongation at break of Examples 1-7 was 7.0%-10%, which was much higher than that of Comparative Example 1 (4%) and Comparative Example 2 (3%). By embedding the flexible polyether segments into the epoxy network through chemical bonds, the flexible chains can absorb stress and improve the elongation at break. In contrast, the comparative examples had poor toughness due to the rigid structure of the epoxy resin.
[0081] Compared with Comparative Example 1, the tensile strength of Examples 1-6 was 66.9-67.5 MPa, which was close to that of Comparative Example 1 (68 MPa). This shows that the epoxy end-capping process improves toughness without sacrificing strength, and avoids phase separation through chemical bonding.
[0082] Compared to Example 1, Comparative Examples 3 and 4 show that Example 1 introduced epoxy groups by reacting glycidyl with NCO to form a "polyurethane-epoxy block" structure with active epoxy groups at the ends. When reacting with amines, the epoxy groups open to form a three-dimensional cross-linked network, while retaining the flexibility of the polyurethane segments, resulting in excellent mechanical properties. In Comparative Example 3, glycidyl was not used for end-capping, and a certain amount of NCO was retained in the system, leading to an increase in elongation but a decrease in strength and the occurrence of foaming. In Comparative Example 4, glycidyl was not used for end-capping; the polyurethane prepolymer reacted with the hydroxyl and epoxy groups of E-44 to form a random copolymer. The epoxy groups were not directionally end-capped, and when reacting with amines, the cross-linking points were randomly distributed, resulting in a decrease in the mechanical properties of the material.
[0083] Compared with Example 1, Comparative Example 5 uses non-flexible polyether, which reduces the elongation at break and increases the exothermic peak temperature. This indicates that flexible polyether plays a key role in increasing the elongation at break of epoxy adhesive and has an important effect on slowing down the crosslinking reaction between epoxy resin and amine curing agent.
[0084] Compared with Example 1, Comparative Example 6 has a large number of polyurethane segments (flexible) in the epoxy-terminated polyurethane epoxy resin, resulting in fewer rigid crosslinking points (epoxy groups). If used alone, the crosslinking network after curing is too loose and the strength is insufficient. Therefore, in order to ensure crosslinking density and mechanical strength, the epoxy-terminated polyurethane epoxy resin still needs to be mixed with conventional epoxy resins (such as bisphenol A type and bisphenol F type).
Claims
1. A method for preparing an epoxy-terminated polyurethane epoxy resin, characterized in that, Includes the following steps: (1) Dehydrate the segment-flexible polyether polyol and then react it with isocyanate at 70-80°C under inert gas protection for 2-3 hours to obtain a polyurethane prepolymer. The segment-flexible polyether polyol is at least one of polyoxypropylene polyol, polytetrahydrofuran polyol or polyoxyethylene-propylene oxide copolymer polyol. (2) Add epoxy resin to polyurethane prepolymer and react at 60-70°C for 2-3 hours; add small molecule epoxy compound and organotin catalyst, and react at 50-55°C until NCO groups are completely eliminated to obtain epoxy-terminated polyurethane epoxy resin, wherein the small molecule epoxy compound is glycidyl ether.
2. The method for preparing epoxy-terminated polyurethane epoxy resin according to claim 1, characterized in that, The organotin catalyst is at least one of dibutyltin dilaurate or stannous octoate.
3. An adhesive containing the epoxy-terminated polyurethane epoxy resin obtained by the preparation method of claim 1 or 2, characterized in that, The product comprises the following components by weight: 10-15 parts epoxy resin, 70-75 parts epoxy-terminated polyurethane epoxy resin, 19-21 parts amine curing agent, and 8-15 parts thermally conductive filler.
4. The adhesive according to claim 3, characterized in that, The thermally conductive filler is at least one of alumina, aluminum hydroxide, or aluminum nitride.
5. The adhesive according to claim 3, characterized in that, The amine curing agent is at least one of isophorone diamine, m-phenylenediamine, or p-phenylenediamine.
6. A method for preparing the adhesive according to any one of claims 3-5, characterized in that, Includes the following steps: (1) Mix the epoxy resin, epoxy-terminated polyurethane epoxy resin and thermally conductive filler evenly; (2) Add amine curing agent, mix, and obtain adhesive.
7. The application of the adhesive according to any one of claims 3-5 in the fields of aerospace, electronics, or machinery manufacturing.
Citation Information
Patent Citations
Polyurethane modified epoxy resin adhesive and preparation method thereof
CN116285831A
Epoxy-terminated polyurethane flexibilizer for bridge and tunnel pavement, and preparation and use methods thereof
CN119529218A
